Identifying Rejection Response of the COVID-19 Vaccination Program in the View of Elderly Community in Palembang - Suzanna, Suzanna; Natosba, Jum; Fatriansari, Asih (Universitas Aisyah Pringsewu, 2022)
The general public's willingness to be vaccinated against COVID-19 is the first step toward establishing a high vaccination rate and managing the pandemic. However, because some people refuse to take the vaccine, vaccine indecision is one of the greatest barriers to managing a pandemic. The objective of this study is to describe the experience of the elderly refusing to be vaccinated against COVID-19. This research is a qualitative study with an empirical phenomenological approach and uses in-person interviews with the time that has been mutually agreed between researchers and informants. Informants are recruited through purposive sampling with criteria for inclusion of elderly age and do not want to be vaccinated. This study reached saturation when the number of participants reached 6 people. Data analysis was administered through Haase's adaptation of the Colaizzi method used to analyze the transcribed. Based on the theme formed, the initial theme is the rejection of the presence of vaccination programs, deep doubts about the validity of the vaccine, mistrust about the content and benefits of the vaccine and the determination of the elderly to maintain rejection. The problem of vaccine doubt is influenced by many factors both sourced from internal and external, and modifications are needed to the internal and external factors. Abstrak: Kesediaan masyarakat umum untuk menerima vaksinasi COVID-19 adalah langkah pertama untuk mencapai tingkat pengambilan vaksinasinasi yang tinggi dan mengendalikan situasi pandemi. Namun, keragu-raguan vaksin merupakan salah satu kendala utama untuk mengendalikan pandemic karena beberapa individu menolak untuk divaksin. Penelitian ini bertujuan untuk menggambarkan pengalaman lansia menolak untuk di vaksinasi COVID-19. Pada penelitian ini menggunakan metode kualitatif dengan pendekatan fenomenologi empiris dan menggunakan wawancara langsung dengan waktu telah disepakati bersama antara peneliti dengan informan. Informan direkrut melalui purposive sampling dengan kriteria inklusi usia lansia dan tidak mau divaksin. Penelitian ini mencapai satu rasi ketika jumlah partisipan mencapai 6 orang. Analisis data dilakukan melalui adaptasi Haase dari metode Colaizzi digunakan untuk menganalisi straskrip. Berdasarkan tema yang terbentuk tema awal yaitu penolakan terhadap kehadiran program vaksinasi, keraguan mendalam terhadap kehalalan vaksin, ketidak percayaan mengenai kandungan dan manfaat vaksin dan keteguhan lansia untuk mempertahankan penolakan. Masalah keraguan vaksin dipengaruhi oleh banyak faktor baik yang bersumber dari internal maupun eksternal, dan diperlukan modifikasi pada faktor internal maupun eksternal tersebut.